Effect of mass rearing and gamma irradiation on the mating behaviour of Eldana saccharina. Issue 2 (23rd September 2016) - Mudavanhu, Pride; Addison, Pia; Conlong, Des E.
Abstract: At low doses of radiation, F1 sterility of the sugarcane stalk borer, Eldana saccharina Walker (Lepidoptera: Pyralidae), can be attained. This bodes well for progression of the sterile insect technique (SIT) as part of an area‐wide integrated pest management strategy against this pest of economic importance. However, success of the SIT is dependent on mating ability and performance of the mass‐reared sterile insects once released into the field. Mating behaviour of non‐irradiated laboratory‐reared male E. saccharina moths and those subjected to radiation (150, 200, or 250 Gy) was investigated in still‐air cage laboratory trials. Video technology was used to determine whether mass rearing and irradiation of adult moths altered their performance in lek formation and mating success, compared to their untreated wild counterparts. Mating frequency, mating duration, onset of mating, and calling during the first two scotophase periods following adult eclosion were used to make these assessments. Results indicated that both irradiated and non‐irradiated laboratory‐reared males are able to form leks and mate with wild females, and are therefore as effective as their wild counterparts with regards to mating performance. However, a quantitative departure of male mating behaviour away from that exhibited by wild males was observed in the non‐irradiated and irradiated laboratory males. These commenced calling and mating earlier than wild males in both scotophases, except for those irradiated at 250 Gy in the case of mating onset. The mating duration of treated males was similar to that of the untreated wild males, except for those irradiated at 150 Gy, which was significantly higher. Our study provides evidence that increasing radiation dose negatively impacts on performance of laboratory‐produced moths relative to their wild counterparts, which in turn could affect the efficacy of the SIT. At 150 and 200 Gy, these parameters are not affected significantly when compared to untreated wild males, and thus these radiation doses can be used safely. However, at higher doses negative effects do become evident.